Overexpression of Global Regulator Talae1 Leads to the Discovery of New Antifungal Polyketides From Endophytic Fungus Trichoderma afroharzianum - Ding, Zhuang; Wang, Xiao; Kong, Fan-Dong; Huang, Hui-Ming; Zhao, Yan-Na; Liu, Min; Wang, Zheng-Ping; Han, Jun (Frontiers in microbiology, 2020)
Transcription regulation caused by global regulators exerts important effects on fungal secondary metabolism. By overexpression of the global regulator Talae1 in a Ficus elastica -associated fungus Trichoderma afroharzianum , two structurally new polyketides ( 1 and 2 ) that were newly produced in the transformant were isolated and identified. Their structures, including the absolute configurations, were elucidated through a combination of high resolution mass spectrometer (HRMS), NMR, and electronic circular dichroism (ECD) calculations. The growth inhibitory activities of compounds 1 and 2 were evaluated against four bacteria and six plant-pathogenic fungi. Compound 1 showed the highest antifungal activity against Botrytis cinerea and Fusarium oxysporum f. sp. nicotianae with MIC of 8 μg/ml. To the best of our knowledge, this is the first study to report on the application of the global regulator in T. afroharzianum to activate the biosynthesis of bioactive secondary metabolites.